Intrathoracic lipoma in the horizontal fissure of the right lung: a case report. Issue 9 (9th September 2021) - Nakajima, Eiji; Takahashi, Hidenobu; Kajiwara, Naohiro; Furukawa, Kinya; Ishizumi, Taichiro; Kataba, Hiroaki; Okubo, Mitsuru; Hirano, Hiroshi; Ikeda, Norihiko
Abstract: Lipomas are benign tumors that originate from mesenchymal tissue, such as subcutaneous tissue. Intrathoracic lipomas are rare, and they can occur in the chest wall, mediastinum and bronchi. In the present case, the patient had an intrathoracic lipoma that was located in the horizontal fissure of the right lung. Retrospective review of chest radiographs taken at a previous health checkup confirmed that the tumor was growing. The patient had no symptoms, and computed tomography and magnetic resonance imaging suggested that the tumor was a hamartoma. The tumor was resected by video-assisted thoracic surgery, and was diagnosed by pathological analysis as an intrathoracic lipoma consisting of no atypical fats.